EFEKTIVITAS PENYAMPAIAN KABAR BAIK MELALUI MEDIA SOSIAL YOUTUBE BERDASARKAN SUDUT PANDANG MAHASISWA SEKOLAH TINGGI TEOLOGI DUTA PANISAL JEMBER - Yusak Noven Susanto (Alucio Dei, 2021)
The delivery of the gospel is a task mandated by the Lord Jesus Christ to his disciples. This does not stop with the disciples of Jesus Christ, but also to the Apostles, the Fathers of the Church, to all believers. Seeing the rapid development of the times in the field of Information and Communication Technology, social media has become the most popular media for everyone today. In a survey conducted by a competent survey institution, it was stated that almost all humans have social media. From this it is also followed by the development of the delivery of gospel which is packaged in interesting content on social media. Through a qualitative approach using a descriptive method, the researcher wants to know the views of STT Duta Panisal students regarding the effectiveness of delivering gospel through social media Youtube.